Using unusable frequencies [solid-state terahertz laser]. - Mullins, J. (IEEE spectrum)
Semiconductor engineers have an embarrassing secret: a nasty hole in the electromagnetic spectrum that they cannot fill, between about 0.3 THz and 30 THz. The terahertz gap, to give the hole its name, had always eluded them until May 2002, when a consortium of European scientists announced a solid-state terahertz laser that for the first time throws this part of the electromagnetic spectrum open to use. The development of this laser is briefly discussed